To What Extent Do Professors Comply with Provisions of Code of Ethics and Professional Conduct - Rfou, Ahmad. N Al- (International Journal of Social and Administrative Sciences, 2021)
The purpose of this study is to determine the degree to which the professors at Tafila Technical University (TTU) comply with the provisions of the Code of Ethics and Professional Conduct from the point of view of ethics students at the university. To achieve this goal, this study uses both primary and secondary sources of data. The data was collected using a questionnaire containing the provisions of the Code of Ethics and Professional Conduct. The data was collected, sorted, edited and analysed using a Statistical Package for Social Science (SPSS 18.0). The results reveal that ethics students strongly agree or agree that the behaviour of TTU professors largely complies with the Code of Ethics and Professional Conduct. More specifically, the variables include: preserve public resources and the university’s interests, property and assets, dealing with superiors, dealing with colleagues and commitment to performing job duties. Respondents’ views of professors' compliance with the Code of Ethics and Professional Conduct with regards to dealing with customers (students) were moderate. The study recommends that the university must issue its own academic conduct code to regulate the relationship between professors and students and raise awareness among academics of the need to adhere to academic ethical practices.